The good old discovery-justification distinction: Remarks on Melogno’s analysis of a Kuhnian account. - García, Pío; Ilcic, Andrés A. (Revista Estudios de Filosofía)
The discovery-justification distinction stands as a pivotal issue within 20th-century philosophy of science. It subtly underpins many foundational topics and concepts pertinent to our comprehension of knowledge. Thomas Kuhn’s contributions are indispensable in this regard, with his critiques playing a pivotal role in shaping both his initial model of scientific progress and its subsequent revisions. Kuhn addressed this dichotomy head-on in the first of his Thalheimer Lectures, presented in 1984. In this paper, we revisit Pablo Melogno’s (2019) examination of Kuhn’s engagement with this theme. Concurring with Melogno, our analysis extends his interpretation by exploring Larry Laudan’s objections to certain research programs focused on a logic of discovery. We further scrutinize specific assumptions about discovery heuristics that have been misinterpreted within Laudan’s methodological framework, particularly the one stemming from Herbert Simon’s pioneering work. By synthesizing these perspectives, we aim to set up a preliminary framework for a more refined understanding of how history and philosophy of science inform the epistemic practices of agents operating with bounded rationality.